(3YbO GdJhQjO aj ejRGf Gdabg GdESdGejs - (3Ydi eMeO Ydi(B, (3bGSes ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2005)
(3JYQja YbO GdJhQjO hYdGbJg HZjQg eeG bO jTJHg Hg, eTQhYjI YbO GdJhQjO aj Gdabg GdGSdGej, UhQ YbO GdJhQjO hMce cd efgG, eOi LhGR aQV ZQGeGJ eGdjI Ydi GdehQOjf(B.s
(3GdeQGLY U(B.147s
Keywords: (3GdGSJjQGOs; (3GdJhQjOs; (3GdYbhOs; (3Gdabg GdGSdGejs